Peran Komunitas Sekolah Dalam Mengembangkan Enam Dimensi Profil Pelajar Pancasila - Bartia Yulinda; Muhariyanti Muhariyanti; Tiara Risdayanti; Delvianty Delvianty; Erlina Saputri (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
This study was motivated by the important role of the school community in supporting the successful implementation of the Pancasila Student Profile as part of the Merdeka Curriculum. The purpose of this study was to analyze how principals, teachers, students, parents, and school committees contribute to the development of the six dimensions of the Pancasila Student Profile. The research used a qualitative approach with a case study design, involving in-depth interviews, observations, and documentation studies conducted at a secondary school during the period from August to October 2025. The results showed that the development of all dimensions of the Pancasila Student Profile was greatly influenced by the quality of collaboration within the school community. The principal plays a role in strengthening school policies and culture, teachers become facilitators in project-based learning, students take an active role as drivers of collaborative activities, while parents and committees provide moral support and program facilities. These findings imply that the success of strengthening the Pancasila Student Profile does not only depend on the curriculum structure, but also on the synergy of the school ecosystem that is created in a sustainable manner.